A Value Chain Based Strategic Management Accounting Model for Private Higher Education Institutions - Minggu, Angela Merici; Aboladaka, Jusuf; Aleng, Yohana Lince; Manu, Christian Daniel; Kase, Alfred G. O. (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the development of a value chain based strategic management accounting model in private higher education institutions. The issue has become increasingly important in a competitive higher education environment, where institutions are required to manage academic and managerial activities more strategically to create value and sustain competitiveness. Using a qualitative case study approach, the study was conducted across three private higher education institutions. Data were collected through in depth interviews, observations, and document analysis, and were examined using open coding, axial coding, and selective coding procedures. The analysis focused on identifying the interdependencies among primary and support activities within the institutional value chain and assessing their contributions to value creation. The findings show that value creation is achieved through the integration of academic functions and support systems, while strategic management accounting plays an important role in generating relevant cost and performance information for managerial decision making. This integration contributes to stronger institutional reputation, improved accreditation outcomes, and greater financial sustainability. The study concludes that the proposed model can support competitive advantage by aligning value chain activities with strategic information needs, thereby strengthening managerial responsiveness and long term institutional performance.